Status Competition and Implicit Coordination: Based on the Role of Knowledge Sharing and Psychological Safety - Xiao, Jiuling; Xue, Yushan; Peng, Yichen; Wang, Jiankang (Frontiers in Psychology, 2022)
Status competition has become an important research topic in the field of organizational behavior. Based on coordination theory and status competition theory, this paper explores the impact mechanism of employees’ different status competition behaviors on implicit coordination from the perspective of individual motivation. It also explores the mediating role of knowledge sharing and the moderating role of psychological safety between status competition and knowledge sharing. The empirical study was carried out with a sample of 367 employees of 44enterprises. The research results show the following findings: (1) Status competition has a differentiated impact on implicit coordination. Prestige-type status competition has a significant positive impact on implicit coordination behavior, while dominant-type status competition has a significant negative impact on implicit coordination behavior. (2) Knowledge sharing plays a mediating role between status competition (prestige-type status competition, dominant-type status competition) and implicit coordination. (3) Psychological safety positively moderated the relationship between prestige-type status competition, dominant-type status competition and knowledge sharing. The results reveal the mechanism between status competition and implicit coordination, which plays an important role in enterprise management and human resource management practice.